Factors of thermodynamical approach to buildings life cycle / Pastato gyvavimo ciklo termodinaminio vertinimo veiksniai - Martinaitis, Vytautas (Journal of Civil Engineering and Management, 1996)
The article suggests that non-industrial buildings in Lithuania consume half the final energy including appr. 70% heat produced in electric power plants and boiler-houses. In order to ensure standard heating and ventilation conditions for these buildings in terms of climate parameters of a normal year it would require heat consumption of some 22 TWh. However, the energy is required not only for operation and maintenance of the building (for active microclimatic conditioning systems—AMCS), but also for setting up the building (for passive microclimatic conditioning systems—PMCS). The above input is therefore determined by technological level in the building and building materials industries. Rather exact evaluations show that in the course of several next years already, primary energy consumption used for a building maintenance shall be equal to that used while construction thereof. In terms of a building life cycle, this is a fairly short term. Therefore these buildings in terms of energetic approach make an intensive energy-consumption system. It is hereby suggested to apply an exergic analysis for a life cycle of a building under certain climatic conditions and PMCS and AMCS combinations defined by the local produce technology level. Using solely economical (both direct or derived) criteria for this intention is therefore insufficient, because the reliability of economic forecasts for longer prospect falls below any other forecasts of physical quantities. As an example for this, a globally-ecological evaluation of energetic systems based on thermodynamics is therefore presented, and is characterised by thermo-economic and exergo-economic criteria.Further, the article provides formulas and indices for thermodynamic evaluation of climatic conditions which indicate minimum requirements of exergy for operation of AMCS. Furthermore, MCS operating points and zones characteristic of different climatic regions are provided. Tasks for MCS thermodynamic analysis have been formulated to include the processes of production of building and insulation materials, and construction erection process. These should be considered the first three stages of the above task:- indices of present exergic input in production of materials;- forecast of potential exergic input in production of materials;- thermodynamic optimisation of technological processes and equipment of building materials.It is therefore considered, that the integration of separate exergic loss components of building life cycle into a general optimisation task shall enable establishment of thermodynamically-optimum combination of exergic use in the buildings under concrete climatic conditions. This would launch, apart from economic, social and ecological aspects, an approach for handling strategic issues of construction and energetic interaction.Article in Lithuanian.First Published Online: 26 Jul 2012